Unlocking the Mystery: Comprehensive Analysis and Insights on Strengthening Organizational Defense - Mohanty, Biswajita (Journal of Research in Science and Engineering, 2025)
This paper comprehensively analyzes the attacks and intrusions by the Lapsus group. Lapsus is notorious for its high-profile attacks on major corporations and governmental entities. This study dives into the modus operandi of Lapsus and their tactics, techniques, and procedures (TTPs). This paper analyzes notable cyber compromises to produce actionable insights for organizational cybersecurity enhancements. This research examines case studies of Lapsus's significant attacks, including the intrusions into Okta, NVIDIA, and Microsoft, to understand the group's operational patterns, target selection, and the sophisticated nature of its campaigns.